The Oxford handbook of information and communication technologies - Mansell, Robin (Oxford : Oxford University Press, 2009)
The production and consumption of Information and Communication Technologies (or ICTs) have become embedded within our societies. This handbook is about the many challenges presented by ICTs. It sets out an intellectual agenda that examines the implications of ICTs for individuals, organisations, democracy and the economy.
Originally published: 2007.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Information technology -- Handbooks, manuals, etc; Telecommunication -- Handbooks, manuals, etc